Isolation, Identification, and Application of Endophytic Fungi from Lavandula stoechas L.: Mitigating Salinity Stress in Hydroponic Winter Cereal Fodder - Carlos García-Latorre; María José Poblaciones (Agronomy)
Soil and irrigation water salinity is a growing global problem affecting farmland, due to poor agricultural practices and climate change, leading to reduced crop yields. Given the limited amount of arable land and the need to boost production, hydroponic systems offer a viable solution. Additionally, endophytic fungi have been shown to mitigate salinity effects through symbiosis with plants. This study evaluated three endophytic fungi isolated from Lavandula stoechas L. in the grasslands of Extremadura (i.e., Diplodia corticola L11, Leptobacillium leptobactrum L15, and Cladosporium cladosporioides L16) for their ability to improve hydroponic forage production under saline conditions. In vitro experiments were conducted assessing plant growth promotion and fungal growth under salinity, followed by research evaluating the impact of fungal inoculation on hydroponic wheat (Triticum aestivum L.) and barley (Hordeum vulgare L.) forages irrigated with NaCl solutions (0, 100, and 200 mM). The results showed improved fungal growth and production of plant growth-promoting substances, which could explain the improved plant germination, shoot and root length, fresh and dry weight, and yield of inoculated plants growing under salinity. Plants inoculated with L15 or L16 showed the best performance overall. L15 demonstrated broader bioactivity in vitro, potentially explaining its superior performance in both wheat and barley growth. Conversely, L16 was more effective in barley, while L11 was beneficial in wheat but detrimental in barley. This study provides a preliminary exploration of the capabilities of these fungi and their optimization for hydroponic forage production.